Gender Differences in Motivation - Shazia Gul , Maher Bano (Pakistan Journal of Psychology, 2012)
The present study investigated gender differences with reference to achievement, affiliation and power motives as they are depicted on media. For this purpose one hundred and two Urdu drama serials telecast by five Pakistan television channels were randomly selected. The method of content analysis was used for identifying relevant motive imageries by using the criteria developed by McClelland and Steele (1972). It was hypothesized that male characters will be depicted in achievement and power related motives more than the female characters and female characters will be presented in affiliation motive than the male characters. Chi square was computed to determine differences in these motives as reflected in their sentences. Male characters were found to be high on these three motives than the female characters, thus approving the hypotheses for achievement and power motives but not for affiliation motive. Keywords: gender differences, motive, achi